Chemostratigraphy of Jurassic-cretaceous Italian carbonate platforms - Woodfine, R; Richard Gareth Woodfine (2002)
﻿ Samples of shallow-water carbonates were collected from Jurassic and Cretaceous Italian carbonate platforms and subjected to petrographic, diagenetic and chemostratigraphic analyses (87Sr/86Sr, δ13Ccarb, δ13Corg, δ18O). In general, the new chemostratigraphic data generated reflect trends established by previous work, some of which has been carried out on biostratigraphically calibrated reference sections. Consequently, chemostratigraphic correlations (87Sr/86Sr, δ13Ccarb) of isotope profiles taken from platform carbonates with well-dated reference sections have allowed the application of high-resolution dating frameworks to the biostratigraphically poorly constrained carbonate platforms. The increased resolution in dating of the Italian carbonate platforms has, furthermore allowed a detailed investigation into the facies response of these carbonate platforms to major geological events. In particular, platform responses to oceanic anoxic events and other periods of major perturbation in the global carbon cycle are analysed (early Toarcian, Aalenian-Bajocian, Oxfordian-Tithonian, Valanginian-Hauterivian, Aptian-Albian, Cenomanian-Turonian, Coniacian-Santonian). Lower Jurassic levels of the Trento Platform record platform devastation in the early Toarcian synchronous with a major negative δ13Ccarb excursion, followed by platform recovery synchronous with a pronounced δ13Ccarb positive excursion and return to background values. The Campania-Lucania Platform shows negligible response to the oceanographic events of the early Toarcian even though the characteristic carbon-isotope profile is readily identifiable. The Trento Platform drowned at approximately the Aalenian-Bajocian Stage boundary, synchronously with a reproducible negative followed by positive δ13Ccarb excursion, whereas the Campania-Lucania Platform underwent a facies transition from oolite to cyclically bedded micrite. The Friuli Platform showed negligible depositional response to the carbon-cycle perturbations of the Kimmeridgian-Tithonian, Valanginian-Hauterivian, Aptian-Albian and Cenomanian- Santonian (as registered in the δ13Ccarb record). The Campania-Lucania Platform registered flooding and increased levels of organic-matter preservation coincident with pronounced positive δ13Ccarb excursions at Cenomanian-Turonian and Coniacian-Santonian levels. Observations on the responses of carbonate platforms to oceanographic conditions during periods of global carbon burial lead to the conclusion that temperature excess is a hitherto neglected control on global carbonate accumulation rates.